Globular CTRP3 promotes mitochondrial biogenesis in cardiomyocytes through AMPK/PGC-1α pathway - Zhang, Cheng-Lin; Feng, Han; Li, Li; Wang, Jin-Yu; Wu, Dan; Hao, Yan-Ting; Wang, Zheng; Zhang, Yan; Wu, Li-Ling (Biochimica et biophysica acta. General subjects, 2017)
Mitochondrial biogenesis is crucial for the maintenance of mitochondrial function and cellular homeostasis. C1q/tumor necrosis factor-related protein-3 (CTRP3) is an adipokine that owns multiple functions on metabolic and cardiovascular diseases. However, whether CTRP3 affects mitochondrial biogenesis in cardiomyocytes remains unknown. Neonatal rat ventricular myocytes were cultured and treated with globular CTRP3 (gCTRP3). The expression of mitochondrial biogenesis related genes was measured by real-time PCR and western blot analysis. Mitochondrial morphology was assessed by a transmission electron microscope. ATP content, oxygen consumption rate (OCR), and sirtuin1 activity were measured with commercial kits. gCTRP3 increased the expression of peroxisome proliferators activated receptor-γ co-activator-1α (PGC-1α), nuclear respiratory factor 1 (NRF-1), NRF-2, mitochondrial transcription factor A (TFAM), cytochrome B, and oxidative phosphorylation complexes III and V, and increased mitochondrial cristae components and OCR. Additionally, gCTRP3 enhanced mitochondrial DNA copy number and ATP content, while the induction was inhibited by knockdown of PGC-1α via small interfering RNA. gCTRP3 increased phosphorylation of AMP-activated protein kinase (AMPK), whereas adenine 9-β-d-arabinofuranoside (AraA), an AMPK inhibitor, attenuated gCTRP3-mediated induction of NRF-1, TFAM, and complexes III and V. gCTRP3 increased both the expression and activity of sirtuin1, whereas inhibition of sirtuin1 by EX-527 attenuated gCTRP3-induced responses. Meanwhile, gCTRP3-mediated activation of sirtuin1 was attenuated by AraA. Moreover, gCTRP3 restored the reduction of sirtuin1, PGC-1α, NRF-1, complex III and ATP content induced by hypoxia-reoxygenation injury. CTRP3 promotes mitochondrial biogenesis in cardiomyocytes via AMPK/PGC-1α pathway. CTRP3 is an endogenous modulator for mitochondrial biogenesis, and may protect cardiomyocytes by ameliorating mitochondrial dysfunction. •CTRP3 promotes mitochondrial biogenesis in neonatal rat cardiomyocytes.•AMPK and PGC-1α are required in CTRP3-induced mitochondrial biogenesis.•CTRP3-induced PGC-1α deacetylation is mediated by SIRT1.•CTRP3 protects against H/R injury by ameliorating mitochondrial dysfunction.